Respostas

2014-03-27T10:55:25-03:00
B/4 = c/2             b+c = 90  
b/2 = c                b = 90 - c
b=2c 
Substituindo , teremos : 
 90 - c = 2*c          b= 2*c 
90 = 2*c +c           b = 2*30
90 = 3*c                b = 60 
c = 30  
1 5 1
2014-03-27T11:28:01-03:00
B    c
--    --
4    2 

2b=4c
  b=4c
      ---
       2
b + c = 90

4c + c =90
---
2

Tira o mmc = 2

2:2=1*4c=4c
2:1=2*c=2c
2:1=2*90=180

4c + 2c = 180
6c=180
  c=180
      ---
       6
c=30

b + c = 90
b + 30 = 90
b=90-30
b=60


Entao b + c= 90
          60+30=90